Sex-Specific differences in running injuries: a systematic review with meta-analysis and meta-regression - Hollander, Karsten Peter; Rahlf, Anna Lina; Wilke, Jan; Edler, Christopher; Steib, Simon; Junge, Astrid; Zech, Astrid (Sports medicine, 2021)
Running is a popular sport with high injury rates. Although risk factors have intensively been investigated, synthesized knowledge about the differences in injury rates of female and male runners is scarce.